Perancangan Ulang Kursi Kuliah Konvensional Menjadi Desain yang Lebih Ergonomis untuk Mahasiswa Institut Teknologi PLN - Ruspendi; Utami Wahyuningsih; Adilla Khairani; Luh Putu Veny Ratih Krisnandewi (Jurnal Industri dan Teknologi Samawa, 2025)
Lecture chairs are one of the important facilities that must be owned by a university in the implementation of the teaching and learning process. Not limited to being available, but more than that, lecture chairs must also be comfortable and safe when used by students when attending lectures. Safe and comfortable chairs are needed so that students do not feel sore or experience other complaints after using lecture chairs for hours. This research aims to redesign conventional lecture chairs to be more ergonomic by using anthropometric data from PLN Institute of Technology. The data collection technique involves direct measurements of the subject's body dimensions to obtain accurate results. The method used in this study is the anthropometric method. The stages carried out start from anthropometric measurements, data adequacy and uniformity tests and make lecture chair designs. The results of the analysis show that the proposed chair design includes adjustment of the height of the backrest, height and width of the seat base, length of the writing base, as well as the length of the chair, taking into account the principle of ergonomics. From the calculation results, it was obtained that the seat design was 51cm in height, 66cm in height in the writing base, 47cm in height in the seat, 40cm in width, 55.16cm in length and 54.50cm in length. This design is expected to contribute to creating better educational facilities and improving the health and comfort of students.